2020
DOI: 10.1002/alr.22548
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis transmembrane conductance regulator function, not TAS2R38 gene haplotypes, predict sinus surgery in children and young adults with cystic fibrosis

Abstract: Background Chronic rhinosinusitis symptomatology begins in early childhood individuals with cystic fibrosis (CF). Cystic fibrosis transmembrane conductance regulator (CFTR) function contributes to sinus development and disease. Genetic variants of the bitter taste receptor TAS2R38 have been suggested to contribute to sinus disease severity in individuals without CF. Our objective was to explore whether functional TAS2R38 haplotypes and CFTR function are associated with sinus disease or the need for sinus surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 34 publications
0
13
0
3
Order By: Relevance
“…In an Italian population of patients with CFTR mutations and concurrent CRS, the PAV allele was associated with a decreased need for ESS 30 . The third study reported no correlation between the TAS2R38 diplotype and incidence of CRS or need for ESS 31 …”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…In an Italian population of patients with CFTR mutations and concurrent CRS, the PAV allele was associated with a decreased need for ESS 30 . The third study reported no correlation between the TAS2R38 diplotype and incidence of CRS or need for ESS 31 …”
Section: Resultsmentioning
confidence: 91%
“…Finally, there is a lack of institutional and geographic diversity in the included studies. Fourteen studies were done in the United States (Philadelphia [9], 12,16,18,24,26,27,29,37,39 South Carolina [1], 25 West Virginia [1], 20 Colorado [2], 38,40 and unspecified [1] 31 ), 5 in Italy, 17,19,28,30,32 1 in Canada, 21 1 in Poland, and 1 in Australia 23 . Despite the leading role of the University of Pennsylvania in pioneering this field and conducting 9 of 14 of the included US studies, increased genetic and geographic diversity of patients will be important given inherent differences in the distribution genetic of TR genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of T2Rs in upper airway defense is supported by observations that patients homozygous for the AVI TAS2R38 polymorphism, which renders the T2R38 receptor non-functional, have increased frequency of gram-negative bacterial infection (18), have higher levels of sinonasal bacteria in general (45,46) and specifically have higher levels of biofilmforming bacteria (47), have higher frequency of chronic rhinosinusitis (48)(49)(50)(51), and exhibit worse outcomes after functional endoscopic sinus surgery (52). One study has suggested that TAS2R38 genetics may also play a role in cystic fibrosis P. aeruginosa infection (53), though other studies have suggested that TAS2R38 may not be a modifier gene in CF (54,55).…”
Section: Introductionmentioning
confidence: 99%
“…This has been further validated in linkage studies, 72 and mutations appear to be predictive of medically recalcitrant CRS and the need for surgical intervention. 73,74 Another noted genetic target is the bitter taste receptor T2R38, encoded by the TAS2R38 gene, which plays a role in sinonasal epithelial defense against gram-negative organisms (eg, Pseudomonas aeruginosa) and mucociliary clearance. 75,76 This gene is prone to polymorphisms that may affect innate host defense mechanisms and increase susceptibility to biofilm formation.…”
Section: Genetic Risk For Crsmentioning
confidence: 99%